Hubungan Senam Diabates terhadap Penurunan Kadar Gula Darah Penderita Diabetes Melitus di Wilayah Kerja Puskesmas Binjai Estate Tahun 2020 - Leny Suarni; Wirda Faswita (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2021)
Diabetes Melitus is a very dangerous disease, because it can cause complications. In 2019, a total of 947 DM patients were registered in the Binjai Estate puskesmas data. Seeing this problem is very important to do diabetes exercise, because through exercise / gymnastics, insulin will work better, so that glucose can enter the muscle cells to be burned. The research objective was to identify blood sugar levels before and after diabetes exercise on blood sugar levels in DM sufferers in the working area of Binjai Estate Health Center. This type of research is a Quasi Experiment with a one group pretest-posttest design. The population in this study were all sufferers of Type 2 diabetes in the Binjai Estate Health Center work area totaling 88 respondents with a sample of 20 respondents, with a purposive sampling technique. Data collection methods for diabetes exercise SOP and digital test tools. The analysis used the chi square test with α = 0.05. The results of the analysis showed that blood sugar levels before the treatment were carried out an average of 239 mg / dL, after treatment an average of 221.45 mg / dL. With a value of 19,679 df 4 and the value of Asymp.Sig. (2-sided) = 0.001 <α = 0.05 means that there is an effect of diabetes exercise on reducing KGD in DM sufferers in the working area of the Binjai Estate Community Health Center. It is recommended for people with diabetes mellitus to always be active in doing diabetes exercises. Keywords: Diabetes Mellitus, Diabetes Exercise, Blood Sugar Levels